Guyana. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Guyana Delegation of 2022 are identified, focus to needs and interests of the country such as; provided a Latin American and Caribbean perspective on the overall topic, “Feeding a Fragile World”, within the context of pervasive health-, conflict-, and climate-related shocks to the global food system; supported CARICOM in the preparation of a Regional Policy for the Importation of Animal and Animal Products; contributed to and actively participated in the CARICOM Agri-Investment Forum and Expo, “Investing in Vision 25 by 2025” in Guyana; actively pursued alliances aimed at agriculture and rural livelihood in Guyana.